A new genus and two new species of congrid eels (Teleostei: Anguilliformes: Congridae) from the Indo-West Pacific, with a redescription and osteology of Chiloconger dentatus - Smith, David G.; Karmovskaya, Emma S. (Zootaxa, 2003)
A new genus and two new species of congrid eels, subfamily Bathymyrinae, are described from the western Indian Ocean and the western Pacific. Kenyaconger gen. nov. differs from all other congrids in having a tubular posterior nostril, opening on the edge of the upper lip behind the labial flange. Kenyaconger heemstrai sp. nov., the only species in the genus, is described from a single specimen collected off the coast of Kenya in the western Indian Ocean. Chiloconger philippinensis sp. nov. is described from the Philippines, the first record of the genus outside the eastern Pacific. It differs from Chiloconger dentatus (Garman, 1899) in several meristic and morphometric characters. Chiloconger dentatus is redescribed from additional material and its osteology is described for the first time. Chiloconger similis Wade, 1946 is reassigned to Paraconger Kanazawa.